Advances in nanoparticle-based radiotherapy for cancer treatment - Meijuan He; Shixiong Chen; Hongwei Yu; Xuhui Fan; Hong Wu; Yihui Wang; Han Wang; Xiaorui Yin (iScience)
Summary: Radiotherapy has long been recognized as an effective conventional approach in both clinical and scientific research, primarily through mechanisms involving DNA destruction or the generation of reactive oxygen species to target tumors. However, significant challenges persist, including the unavoidable damage to normal tissues and the development of radiation resistance. As a result, nanotechnology-based radiotherapy has garnered considerable attention for its potential to enhance precision in irradiation, improve radiosensitization, and achieve therapeutic advancements. Importantly, radiotherapy alone frequently falls short of fully eradicating tumors. Consequently, to augment the efficacy of radiotherapy, it is often integrated with other therapeutic strategies. This review elucidates the mechanisms of radiotherapy sensitization based on diverse nanoparticles. Typically, radiotherapy is sensitized through augmenting reactive oxygen species production, targeted radiotherapy, hypoxia relief, enhancement of antitumor immune microenvironment, and G2/M cell cycle arrest. Moreover, the incorporation of nanoparticle-based anti-tumor strategies with radiotherapy markedly enhances the current state of radiotherapy. Additionally, a compilation of clinical trials utilizing nano-radioenhancers is presented. Finally, future prospects for clinical translation in this field are thoroughly examined.